Union bargaining power, subcontracting and innovation - Beladi, Hamid; Mukherjee, Arijit (Elsevier, 2017)
We show that if a firm can subcontract production to an informal sector, an increase in union power may either increase or decrease innovation. An increase in union power makes the firm worse off irrespective of its effect on innovation. However, in contrast to the usual belief, an increase in union power may increase consumer surplus and decrease union utility by affecting innovation, thus suggesting that a union may not want to be too powerful. An increase in union power may create an ambiguous effect on social welfare. Our analysis provides new insights to the relation between union power and innovation.